Ethnic Domination in Deeply Divided Places The Hegemonic State in Israel and Estonia - Panzano, Guido (Premio Cesare Alfieri «Cum Laude», 2021)
This volume examines the concept of ethnic domination and its manifestations in Israel (within the Green Line) and Estonia. Ethnic domination is a method of managing ethnic differences in multiethnic contexts through asymmetrical power relations, in accordance with an ethnonationalist ideology, whereby a group is subordinated to another holding the power, albeit not intent to directly eliminate the subaltern. The volume compares the predicament of Israeli Palestinian citizens and Estonian Russian-speakers in different dimensions (state-citizenship, government-parliament, parties). Also, the analysis explains the divergent trajectories of the cases: the tightening of the condition of Israeli Palestinian citizens and the democratization of ethnic politics in Estonia.